2015
DOI: 10.1038/srep08746
|View full text |Cite
|
Sign up to set email alerts
|

Latent instabilities in metallic LaNiO3 films by strain control of Fermi-surface topology

Abstract: Strain control is one of the most promising avenues to search for new emergent phenomena in transition-metal-oxide films. Here, we investigate the strain-induced changes of electronic structures in strongly correlated LaNiO3 (LNO) films, using angle-resolved photoemission spectroscopy and the dynamical mean-field theory. The strongly renormalized eg-orbital bands are systematically rearranged by misfit strain to change its fermiology. As tensile strain increases, the hole pocket centered at the A point elongat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 50 publications
7
25
0
Order By: Relevance
“…However, the small electron escape depth in VUV-ARPES experiments has limited most studies to the top layer of oxide thin films. 2,[9][10][11] Most members of the nickel based perovskite oxides RNiO 3 (R is a trivalent rare earth element) exhibit a metal-to-insulator transition as a function of temperature. [12][13][14][15] In addition, a transition from a paramagnetic to an antiferromagnetic ground state is observed in these compounds.…”
Section: © 2017 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…However, the small electron escape depth in VUV-ARPES experiments has limited most studies to the top layer of oxide thin films. 2,[9][10][11] Most members of the nickel based perovskite oxides RNiO 3 (R is a trivalent rare earth element) exhibit a metal-to-insulator transition as a function of temperature. [12][13][14][15] In addition, a transition from a paramagnetic to an antiferromagnetic ground state is observed in these compounds.…”
Section: © 2017 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…These strain-induced structural transformations are central to understand some dramatic changes of physical properties such as metal-insulator transitions observed on LNO thin films and LNO multilayers [3][4][5][6][7][8][9], or to rationalize reported spectroscopic results. For instance, Chakhalian et al [10], Freeland et al [11], and Tung et al [12] reported x-ray absorption results at Ni edges of LNO films grown on LaAlO 3 (LAO) and SrTiO 3 (STO) substrates, which impose compressive and tensile stresses, respectively, supported by first-principles density functional theory (DFT) calculations.…”
Section: Introductionmentioning
confidence: 99%
“…The interest is mainly motivated by a strong similarity of low-spin Ni 3+ ions, having an electronic configuration 3d 7 : t 2g 6 e g 1 , to Cu 2+ ions in the high-temperature superconducting cuprates (HTSCs, with 3d 9 : t 2g 6 e g 3 ). In the HTSC materials, due to their layered structure, the z 2 orbitals are pushed down in energy and are fully occupied, whereas conductivity is confined to the partially occupied x 2 -y 2 orbitals.…”
Section: Introductionmentioning
confidence: 99%
“…LaNiO 3 has already been characterized experimentally via ARPES [14][15][16], optical conductivity [17][18][19], and thermodynamic measurements [20][21][22], as well as theoretically with DFT [23][24][25], DFT + DMFT [6,8,[26][27][28][29], and model system [30][31][32] calculations, and a variety of measurements of m /m have previously appeared (to be discussed more later). ARPES offers a particularly direct measure of a material's mass enhancement via momentum-resolved access to the electronic Green's function, which is the fundamental quantity that characterizes electron propagation in a material:…”
Section: Introductionmentioning
confidence: 99%
“…The MIT temperature is related to the amplitude of the NiO 6 octahedral rotations, which in bulk materials is controlled by the size of the R cation. In addition, studies of ultrathin films of LaNiO 3 grown epitaxially on different substrates [10][11][12][13][14][15] show that both the critical film thickness for an MIT and the coefficient of the T 2 term in the resistivity depend on the value of the epitaxially induced strain. We thus expect that in LaNiO 3 the correlation strength is determined by a subtle interplay between a basic interaction parameter and the precise crystal structure.…”
Section: Introductionmentioning
confidence: 99%